Peran konselor terhadap anak-anak broken home - Romauli Sitohang; Yanto Paulus Hermanto (Davar : Jurnal Teologi, 2022)
Abstract Children who come from broken home families require serious treatment. The role of the counselor is the core of this research, namely how the role of the counselor in helping children from broken home families. This study uses a qualitative research approach. The results of the study related to the counselor's role include understanding the condition of the broken home child, sincere concern, and the appropriate approach taken by the counselor. Key words: role, counselor, children, broken home. AbstrakAnak-anak yang berasal dari keluarga broken home memerlukan penanganan yang serius. Peran konselor merupakan  inti dari penelitian ini, yakni bagaimana peran konselor dalam menolong anak-anak dari keluarga broken home. Penelitian ini menggunakan pendekatan penelitian kualitatif. Hasil penelitian berkaitan dengan peran konselor meliputi memahami kondisi anak broken home, perhatian yang tulus, dan pendekatan yang dilakukan konselor tepat. Kata kunci: peran, konselor, anak-anak, broken home.